Reforma de la ley de gestión ambiental, referente a la contratación de seguros de protección ambiental - Parraga Mendoza, Richard Lorgin (2014)
Ecuadorian law environmental liability insurance and no environmental protection is well established that Article 34 of the Environmental Management Act states that " they serve as instruments for implementing environmental standards, taxes and fines for the protection environmental and sustainable use of natural resources as well as risk insurance and deposit systems, the same that can be used to encourage pro- environmental protection actions." As can be seen in the Environmental Management Act insurance risks to the environment is allowed. The law defines the insurable risk as an uncertain event does not depend on the will of the insurer, the applicant or recipient. Our legislation are not insurable for example, fraud, gross negligence and acts merely potestativos insured. It should be noted that the law speaks only of intent or gross fault of the insured, leaving the door open to ensure the fraud or gross negligence of third parties. Similarly limited assurance criminal sanctions or police nature, which would be under the purview of criminal law. In this area could be any act or omission classified as environmental crimes. It is not yet open discussion that happens to damage or injury to such actions or omissions cause to others Can be insured through liability policies for environmental damage? Ecuadorian legislation, referring to liability insurance, provides that the insurer must meet within the limits specified in the contract pecuniary compensation according to the law applicable to the insured pay civilly liable for damage caused to third parties, made under the contract. Ie liability is the basis of liability insurance. The liability insurance is not insurance to third parties. The insurable risk must be stated in the contract, otherwise it can not be that the insurer assumes the payment of the claim by the insured . The liability insurance is intended to protect the insured's estate from potential harm resulting from a liability incurred. In Ecuador, it is necessary to have policies on environmental protection, not under the current global practice of granting environmental responsibility policies, or have several pools of structured insurance insurance companies, because they are confined to certain economic activities , and individual coverage under liability policies , so the tendency is to ensure environmental risks and environmental pollution through damage liability insurance is maintained. What in my opinion, is restrictive, and that through these policies no protection for the environment affected by environmental damage, but eventually heritage protection official, who is the insured, as are contracted through insurance seeks to compensate victims of an environmental accident has affected his property and his person.